Calculus 8th Edition

Published by Cengage

Chapter 14 - Partial Derivatives - 14.3 Partial Derivatives - 14.3 Exercises - Page 966: 88

Answer

$\dfrac{\partial P}{\partial V}\dfrac{\partial V}{\partial T}\dfrac{\partial T}{\partial P}=-1$

Work Step by Step

Since, $P= \dfrac{mRT}{V} ,V=\dfrac{mRT}{P}; T= \dfrac{PV}{mR}$ ...(1) $\dfrac{\partial P}{\partial T}=\dfrac{\partial}{\partial T}[\dfrac{mRT}{V}]=\dfrac{mR}{V}$ ...(2) and $\dfrac{\partial T}{\partial P}=\dfrac{V}{mR}$ ...(3) From equations (1), (2) and (3), we have $\dfrac{\partial P}{\partial V}\dfrac{\partial V}{\partial T}\dfrac{\partial T}{\partial P}=(\dfrac{-mRT}{V^{2}}) (\dfrac{mR}{P})(\dfrac{V}{mR})$ $\implies \dfrac{-mRT}{PV}=\dfrac{-mRT}{\dfrac{mRT}{V}\times V}=-1$ Thus, $\dfrac{\partial P}{\partial V}\dfrac{\partial V}{\partial T}\dfrac{\partial T}{\partial P}=-1$

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.